Readiness of Internships Program During The Covid-19 Pandemic: Students, School, and Industry Perspective - Shodiq; Sutiman (Jurnal Pendidikan dan Pengajaran, 2022)
The COVID-19 pandemic has made learning at school unable to be carried out face-to-face; this condition has a worse effect on vocational education, which cannot carry out practical learning to prepare students that must carry out internships in industry. This study explores the student readiness level in carrying out internship programs during the pandemic and the other perspective from school and industry. This article focused from the point of view on the results of a mix-method online survey among 160 internship students. Teachers and industry practitioners were also interviewed to corroborate the results of the readiness research. The results show that 4.04% of students had a low level of readiness, 60.18% had a moderate level of readiness, 24.98% had a high level of readiness, and only 10.80% had a very high level of readiness. The school is responsible for preparing their student competence before sending them to the internship program in the industry, even in crises, because the industry is already prepared for exceptional cases like the pandemic. Industry advises schools to prepare students on the competence of motorcycle periodical maintenance. Schools with industry must have special programs planning to prepare students' competence for crises.